Consumo de ciclosporina y tacrolimus en la unidad de trasplante renal del servicio de nefrología del hospital nacional edgardo rebagliati martins – essalud lima, en el periodo julio – diciembre 2008” - Fernández Burga, Nidia Yadira (2009)
The present descriptive, transverse, and retrospective study, had as objective to determinate the characteristics of consume of Cyclosporine and Tacrolimus in the Renal Transplant Unit of Nephrology’s service of the National Hospital Edgardo Rebagliati Martins - ESSALUD in the period on July - December, 2008. The sample in study was shaped by the Units of Ciclosporina and Tacrolimus consumed in the Renal Transplant Unit during this period of time, it was investigates: consume monthly and half yearly of Cyclosporine and Tacrolimus expressed in daily definite dose (DDD) for 100 beds – days, in addition monthly and half year consumer expenditure. The Cyclosporine’s and Tacrolimus consume in the National Hospital Edgardo Rebagliati Martins - ESSALUD during July - December, 2008 was 7.23 DDD/100 beds - days and 26.83 DDD/100 beds – days respectively, that generated an expense of S/. 1858.38 for the Cyclosporine and S/. 14004.12 for the Tacrolimus